2020
DOI: 10.1007/s13187-020-01916-w
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Messaging and Strategies to Promote “SWIFT” Lung Cancer Detection: a Qualitative Study Among High-Risk Individuals

Abstract: Lung cancer (LC) is the most common cancer and the leading cause of cancer mortality globally. A positive association between LC incidence and socioeconomic deprivation exists. High-risk individuals are less likely to be aware of LC and to correctly appraise LC symptoms and seek medical help accordingly. This qualitative study explored strategies to promote early detection of LC among at-risk individuals living in high-incidence areas in Ireland. Five semi-structured focus groups were conducted with 46 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…The cost of GP visits and long waiting times emerged as potential barriers. These ndings are well documented in previous research with at-risk patients [11,14]. However, in the current study, there was no full agreement on how cost impacted on patients with LC symptoms due to the eligibility of most high-risk groups for GP visit/medical cards.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The cost of GP visits and long waiting times emerged as potential barriers. These ndings are well documented in previous research with at-risk patients [11,14]. However, in the current study, there was no full agreement on how cost impacted on patients with LC symptoms due to the eligibility of most high-risk groups for GP visit/medical cards.…”
Section: Discussionsupporting
confidence: 57%
“…The use of a celebrity (i.e., Sir Alex Ferguson) on the cover of the Scottish campaign was also perceived as "catchy." Similar feedback was provided by at-risk individuals in a previous study who appreciated the acknowledgement of their potential fears and the positivity and clarity of the messages in both campaigns, particularly the Scottish one [14]. Of note, the English campaign "Be Clear on Cancer" has been evaluated on several occasions and was found to signi cantly increase LC awareness and help-seeking and reduce the number of patients diagnosed with late-stage LC [28].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Future research should also focus on public health messaging that would help at-risk populations get diagnosed and treated early. For instance, Saab et al (2020) found that individuals at risk for LC favoured public health messages that are "Simple, clear, and honest; Worded positively; Incorporating a shock element; Featuring a celebrity, healthcare professional, or survivor; and Targeted (SWIFT)" (p.1). Participants also recommended using broadcast together with print media within national government-run campaigns in order to promote LC awareness and early detection.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…While recent studies have explored LC help-seeking from the perspective of at-risk populations [ 13 , 19 , 20 ], there has been very little research conducted amongst primary healthcare professionals who play a key role in advising and referring patients who present to them with signs and symptoms suggestive of LC, particularly during the COVID-19 pandemic. Therefore, this study explored perceived barriers to patient help-seeking and strategies to enhance help-seeking for LC signs and symptoms from the perspective of primary healthcare professionals in Ireland.…”
Section: Introductionmentioning
confidence: 99%